Occurrence of imposex in Thais haemastoma: possible evidence of environmental contamination derived from organotin compounds in Rio de Janeiro and Fortaleza, Brazil Ocorrência de imposex em Thais haemastoma: possíveis evidências de contaminação ambiental por compostos organotínicos no Rio de Janeiro e em Fortaleza, Brasil - Marcos Antonio Fernandez; Aricelso Maia Limaverde; Italo Braga de Castro; Ana Cristina Martins Almeida; Angela de Luca Rebello Wagener (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
There are indications that the widespread use of organotin compounds (TBT and TPT) as antifoulings, as stabilizers in plastic and as pesticides, has severely affected several species of marine organisms. The most striking effect of TBT and TPT as hormonal disruptors is the development of male organs in females of gastropods, currently denominated imposex. This syndrome can lead to the sterilization and death of affected organisms. The present work gives an overview of the present state of knowledge on imposex occurrence and reports results of a survey conducted in Guanabara Bay, Rio de Janeiro and in several sites along the coast of Fortaleza, Ceará State. Different stages of imposex development were verified in this survey, however, the most prominent levels appeared associated to known spot sources of TBT and TPT. Existem evidências de que a utilização amplamente disseminada de compostos organoestânicos (TBT e TPT) como antiincrustantes, estabilizadores em plásticos e como pesticidas tenha afetado severamente diversas espécies de organismos marinhos. O mais característico efeito do TBT e do TPT como desreguladores endócrinos é o desenvolvimento de caracteres sexuais masculinos em fêmeas de gastrópodos, conhecido como imposex. Esta síndrome pode levar à esterelização e morte dos organismos afetados. O presente trabalho apresenta uma vista geral ao estado atual do conhecimento sobre a ocorrência do imposex, e reporta os resultados de um estudo conduzido na Baía de Guanabara, Rio de Janeiro, e ao longo da costa de Fortaleza, no Ceará. Diferentes estágios de desenvolvimento do imposex foram verificados neste estudo, os mais proeminentes parecendo associados às fontes pontuais locais conhecidas de TBT e TPT.